Towards achieving CSR global standards in the 21st century: public relations practitioners' struggles and challenges from Malaysian perspectives - Mohd Hasan, Nurul Ain (Lambert Academic Publishin, 2016)
The overarching aim of this book is to explore the current corporate social responsibility (CSR) best practices of Malaysian multinational corporations (MNCs). Specifically, CSR performance is measured against global best practice standards and the role given to public relations in CSR is investigated. This book explores links between CSR and public relations in the context of Malaysian organisations. Case studies are presented in the form of interview data to showcase the many struggles and challenges of Malaysian public relations practitioners. The case studies indicate Malaysian public relations practitioners tend to hold technical roles in CSR and lack leadership roles. It also suggests that CSR communication in Malaysian organisations lack throughness in the 21st century.